Are Your Campus Eco ? A Perception Students About Environmental Education, Jember Indonesia - Anita Dewi Moelyaningrum; Prehatin Tri Rahayu Ningrum (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Global warming is a global issue. Eco campus or green campus is the concepts to resolve the environmental problems. The aim of this research is to analyze how eco is your campus observed from knowledge and students’ perception on environmental sustainability education. The methods of this research are cross sectional study and analytic observational. The total of respondents is 160 students who randomly chosen. Respondents have interviewed about their perspectives on environmental sustainability education especially the eco campus concept. The result of this research showed that 134 respondents (83,75%) had known about the information of the eco campus. There were 77 respondents (48,1%) have the negative attitude, 43 respondents (26.9%) have the positive attitude and 40 respondents (25%) have the neutral attitude about the eco campus. The data showed that 91 respondents have poor behavior toward eco campus concepts (56,9%), 65 respondents good enough (40,6%) and 4 respondents have very good behavior (2,5%). The development of sustainable environment should be educated continuously to the higher students to meet the eco campus sustainability to reduce the global warming.